Effects of Media Formulation, Temperature, and Preservation Period on the Viability of White Oyster Mushroom (Pleurotus ostreatus) Spores - Bertha Aurellia; Ruth Meike Jayanti (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effects of growth medium formulation, storage temperature, and preservation period on the spore viability of the white oyster mushroom (Pleurotus ostreatus). The study employed an experimental method using a split-plot design involving three types of preservation media: Potato Dextrose Broth (PDB), PDB supplemented with 15% paraffin, and corn decoction medium. The treatments were evaluated under two storage temperature conditions, namely 4°C and room temperature at 26°C, across four preservation periods: 2, 4, 6, and 8 weeks. The observed parameters included the time of colony emergence, colony number, and microscopic hyphal morphology. The results showed that all media stored at 4°C were able to maintain spore viability for up to 8 weeks. PDB produced the highest colony numbers, ranging from 224 to 593 colonies, and showed the fastest colony emergence, occurring on days 1 to 2. PDB supplemented with 15% paraffin produced 128 to 248 colonies, with colony emergence on day 2, whereas the corn decoction medium produced 89 to 142 colonies, also with colony emergence on day 2. All treatments stored at room temperature at 26°C became contaminated and therefore failed to maintain spore viability. Microscopic observations indicated that hyphal structures remained normal in all treatments stored at 4°C. Based on colony number and growth rate, PDB stored at 4°C demonstrated better preservation performance than the other media in maintaining the spore viability of Pleurotus ostreatus for up to eight weeks of storage.